METAPHYSICAL LOVE IN TURKISH CULTURE - ÖZEN, YENER (Innovare Journal of Social Sciences, 2023)
What is Love? Is it identifiable? or is it learned by living? It is not as easy as one might think to give a coherent answer to these questions. Scientists, thinkers and artists have defined love in different ways or have tried to explain it. Scientists say that the motive of love begins with birth. This is an important starting point in terms of revealing the source of love. From this point of view, it will contribute to our saying that love begins with the existence of the first human being. At first, people feel lonely and are alone with themselves. Later, as he gets to know the beings and objects outside himself, he enters into some relations with them. If there is no expression of love in these relationships, the person returns to his loneliness again, which creates a feeling of shame in him. This is also a source of guilt and restlessness. As a matter of fact, in the history of humanity, especially in our age, there are millions and billions of people whose needs are not met to love, be loved, adopted. If the conditions continue like this, man can become the preparer and implementer of the great slaughter, that is, the apocalypse. When the biological and trust needs of the person are not met, what can happen when the love and adoption needs are not met, drug addiction, aggression, murder, hippieism, conversion to primitive religions, robbery, war, conflict, etc., in advanced societies such phenomena and events. The reason for such undesirable facts and events is not only lovelessness. There are many economic, political, social and cultural reasons for this. However, one of the important reasons may be that the need to love, be loved and embraced is not met.